Partial Differential Equation for Heat Conduction and Its Solvability - Kovacik, Ondrej; Orsansky, Pavol (Communications - Scientific letters of the University of Zilina, 2010)
This paper deals with the heat conduction equation which is a model of thermomechanical processes in the special case. The considered case is based on the nonstandard type of coefficients in this equation.